Efektivitas Mediasi Sebagai Alternatif Penyelesaian Sengketa Bisnis Di Indonesia - Aura Faraz Az Zahra; Indah Ayu Zhafira; Fatrisia Yuristi; Asep Suherman (CV. ITTC INDONESIA, 2025)
Business disputes in Indonesia have increased along with the development of the business world, but court resolution is considered slow, expensive, and incapable of restoring relationships between the parties. Mediation, as part of Alternative Dispute Resolution (ADR), is a solution regulated normatively through Supreme Court Regulation Number 1 of 2016. This study aims to describe the legal basis for mediation in resolving business disputes and analyze its effectiveness in practice. The research method uses a normative juridical approach with an analysis of legislation, legal literature, and court decisions. The discussion shows that mediation can reduce costs, expedite resolution, and maintain business relationships, but faces obstacles such as a lack of public understanding and uneven quality of mediators.